SQL : a beginner's guide - Oppel, Andrew J.; Sheldon, Robert, 1955- (New York : McGraw-Hill, 2009)
Written to the SQL:2006 ANSI/ISO standard, this easy-to-follow guide will get you started programming in SQL right away. You will learn how to retrieve, insert, update, and delete database data, and perform management and administrative functions. SQL: A Beginner's Guide, Third Edition covers new features, including SQL/XML, and is loaded with updated SQL examples along with notes on using them with the latest RDBMS software versions such as MySQL 5.0, SQL Server 2008, and Oracle Database 11g. Designed for Easy Learning: Key Skills & Concepts--Lists of specific skills covered in the chapter Ask the Experts--Q&A sections filled with bonus information and helpful tips Try This--Hands-on exercises that show how to apply your skills Notes--Extra information related to the topic being covered Self-Tests--Chapter-ending quizzes to test your knowledge Annotated Syntax--Example code with commentary that describes the programming techniques being illustrated
PART I - Relational Databases and SQL -- Chapter 1. Introduction to Relational Databases and SQL -- Chapter 2. Working with the SQL Environment -- Chapter 3. Creating and Altering Tables -- Chapter 4. Enforcing Data Integrity -- Chapter 5. Creating SQL Views -- Chapter 6. Managing Database Security -- Part II - Data Access and Modification -- Chapter 7. Querying SQL Data -- Chapter 8. Modifying SQL Data -- Chapter 9. Using Predicates -- Chapter 10. Working with Functions and Value Expressions -- Chapter 11. Accessing Multiple Tables -- Chapter 12. Using Subqueries to Access and Modify Data -- Part III - Advanced Data Access -- Chapter 13. Creating SQL-Invoked Routines -- Chapter 14. Creating SQL Triggers -- Chapter 15. Using SQL Cursors -- Chapter 16. Managing SQL Transactions -- Chapter 17. Accessing SQL Data from Your Host Program -- Chapter 18. Working with XML Data -- Part IV - Appendices -- Appendix A: Answers to SelfTest -- Appendix B: SQL:2006 Keywords -- Appendix C: SQL Code Used in Try This Exercises -- Index.
Includes index.
Previous ed.: Robert Sheldon's name appeared first on t.p.
1
Keywords: SQL (Computer program language); Relational databases